Integral Sliding Mode Control Design for Electronic Throttle Valve System - AL-Samarraie, Shibly Ahmed; Badri, Alaq Sabah; Mishary, Mustafa H. (Al-Khwarizmi Engineering Journal, 2015)
Abstract One of the major components in an automobile engine is the throttle valve part. It is used to keep up with emissions and fuel efficiency low. Design a control system to the throttle valve is newly common requirement trend in automotive technology. The non-smoothness nonlinearity in throttle valve model are due to the friction model and the nonlinear spring, the uncertainty in system parameters and non-satisfying the matching condition are the main obstacles when designing a throttle plate controller.In this work, the theory of the Integral Sliding Mode Control (ISMC) is utilized to design a robust controller for the Electronic Throttle Valve (ETV) system. From the first instant, the electronic throttle valve dynamics is represented by the nominal system model, this model is not affected by system parameters uncertainty and the non-smooth nonlinearities. This is a consequence of applying the integral sliding mode control. The ISMC consists of two part; the first is the nominal control which is used to control the nominal system, while the second is a discontinuous part which is used to eliminate the effects of the parameters uncertainty and the non-smooth nonlinearities from system model. These features for the ISMC are proved mathematically and demonstrated numerically via seven numerical simulations and for different desired trajectories.  The simulation results clarify that for different system parameters, the ETV behaves as a nominal system. This enables to freely and precisely select the system response characteristics and the time required for the throttle angle to reach the desired value. Moreover the ability to deal with the chattering problem is demonstrated through the worked  simulation tests, where the chattering is eliminated via approximating the signum function by arc tan function. Keywords: Electronic throttle valve, Nonlinear spring model, Integral sliding mode control, Non-smooth model.